LCAS-APT Protocol: Landscape Crop Assessment Survey and Agronomy Prioritization Tool Version 1 - Urfels, Anton; Assefa, Banchayehu; Silva, João Vasco; Aubert, Celine; Samaddar, Arindam; Ajay, Anurag; Schmitter, Petra; Senthilkumar, Kalimuthu; Kumar, Virender; Ragasa, Catherine; McDonald, Andrew J.; Vanlauwe, Bernard (CGIAR Sustainable Farming, 2025)
"The Landscape Crop Assessment Survey (LCAS) and Agronomy Prioritization Tool (APT) is an agricultural data collection and analytics tools that use a lean data approach, focusing on recurrently collecting essential data on crop production practices to drive impactful decision-making in smallholder farming systems, enhance agricultural practices, and tackle productivity and sustainability challenges in diverse farming landscapes. Using mobile technology and geospatial tools, LCAS-APT gathers high-quality, representative data on crop yields, crop management practices, environmental conditions and socio economic factors, in an efficient and costeffective manner. This is achieved through a streamlined 30-minute survey and readily available data cleaning and analytics pipelines. LCAS-APT consists of several components, including: 1. The core component is a modular and lean survey that is available in ODK format (i.e. XLS Form) for ready deployment and customization. a. This survey tool consists of both (i) core / mandatory modules and (ii) a collection of optional modules that may be deployed as follow up or for a subset of farmers depending on financial resource availability and secondary survey purposes. 2. Cleaning and data curation scripts. 3. Descriptive analytics platform for quick initial insights and automated reporting. 4. Connectivity to deeper analytics such as yield gaps analyses."